Basalt fiber reinforced composite material grid for concrete crack resistance and concrete member

By using basalt fiber reinforced composite mesh in concrete structures, the crack problem in concrete construction is solved, crack resistance and durability are improved, and rust swelling and crack expansion are avoided.

CN222667327UActive Publication Date: 2025-03-25JIANGSU LVCAIGU NEW MATERIAL TECH DEV CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202420592448.6
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-03-26
Publication Date
2025-03-25
Estimated Expiration
2034-03-26

AI Technical Summary

Technical Problem

The existing concrete construction technology is prone to cracks during the pouring of large volume concrete, which affects the safety and durability of the structure. The existing crack-resistant mesh materials have poor corrosion resistance, which can easily lead to rust swelling and crack expansion.

Method used

The basalt fiber reinforced composite mesh is used to improve the bonding and tensile properties of the mesh to concrete through the cross structure of transverse and longitudinal limbs and the adhesion of sand and gravel, and control the emergence and development of cracks by adjusting the mesh size and the thickness of the concrete protective layer.

Benefits of technology

Effectively reduce the tensile stress on the concrete surface, control the emergence and development of cracks, improve the crack resistance and long-term durability of concrete structures, and avoid rust swelling and crack expansion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222667327U_ABST
    Figure CN222667327U_ABST
Patent Text Reader

Abstract

The utility model discloses a basalt fiber reinforced composite material grid for concrete crack resistance and a concrete member, the basalt fiber reinforced composite material grid for concrete crack resistance comprises transverse branch strips and longitudinal branch strips, and the transverse branch strips and the longitudinal branch strips are formed by impregnating basalt fiber tows in resin and then curing. The cross sections of the transverse limbs and the longitudinal limbs are flat; the surfaces of the transverse limbs and the surfaces of the longitudinal limbs are hydrophilic surfaces, and gravels adhere to the hydrophilic surfaces of the transverse limbs and the hydrophilic surfaces of the longitudinal limbs. The surfaces of the transverse limb strips and the longitudinal limb strips are hydrophilic surfaces, and the hydrophilic surfaces improve the chemical bonding force of the limb strips and concrete and enhance the bonding performance. Gravel adheres to the hydrophilic surfaces of the transverse limb strips and the longitudinal limb strips, so that the friction force between the limb strips and concrete is improved, and the bonding performance is enhanced. And by setting different mesh sizes and concrete protection layer thicknesses, the concrete protection layer and concrete are cooperatively deformed and jointly stressed, and the comprehensive crack control effect is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model relates to the technical field of concrete construction, in particular to a basalt fiber reinforced composite material grid structure based on concrete crack resistance. Background Art

[0002] When pouring large volumes of concrete, due to its relatively small surface coefficient, the heat release of cement hydration is relatively concentrated, and the internal temperature rises quickly. When the temperature difference between the inside and outside of the concrete is large, cracks are prone to form on the concrete surface. In addition, the thermal expansion coefficients of the steel bars and concrete are inconsistent, so cracks will also form due to temperature changes, affecting the safety of the structure and normal use.

[0003] In the existing mesh anti-cracking technology, ordinary steel bars have poor corrosion resistance and are prone to corrosion and rust expansion; although stainless steel rusts slowly, it is still unavoidable to rust and expand, and the welding points are prone to rust, which destroys the integrity of the mesh. For example, Chinese Patent No. "201310280608.X" discloses a "concrete protective layer anti-cracking method", in which the concrete needs to be poured twice. After the initial setting of the poured concrete and before the final setting, the steel mesh is set and fixed at the designed position, and then the concrete is poured again. Although this invention can increase the strength of reinforced concrete and prevent cracks from forming, the secondary pouring of concrete may affect the strength of the concrete interface. At the same time, the rust expansion of the steel mesh in the later stage will also cause the expansion of old cracks and the generation of new cracks, which will eventually lead to the peeling of the concrete protective layer. Among the composite material meshes, the carbon fiber mesh has the highest strength, but the price is high, and the thermal shrinkage and cold expansion are not used for structural crack resistance; the glass fiber mesh has low strength, poor creep performance and easy brittle fracture, and is not suitable for engineering applications.

[0004] Basalt fiber reinforced composite mesh has the characteristics of corrosion resistance, light weight and high strength, high and low temperature resistance, and a thermal expansion coefficient consistent with concrete. It is arranged in the concrete protective layer as a reinforcing material and cast in one time. It resists the tensile stress on the concrete surface through bonding with concrete, reduces the tensile stress, and thus controls the appearance and development of cracks, including but not limited to cracks caused by temperature changes, shrinkage creep and external loads. It is suitable for adding to new concrete structures to improve their comprehensive crack resistance. Utility Model Content

[0005] The technical problem to be solved by the utility model is to provide a basalt fiber reinforced composite material grid and concrete component for concrete crack resistance, which can improve the bonding with concrete to resist the tensile stress on the concrete surface, effectively control the cracking during the initial pouring, and effectively alleviate and control the development and occurrence of cracks in the concrete over a long period of time and under the action of external loads, and significantly improve the long-term durability of the concrete structure.

[0006] In order to solve the above technical problems, the utility model provides the following technical solutions:

[0007] The utility model firstly provides a basalt fiber reinforced composite material grid for concrete crack resistance, comprising transverse limbs and longitudinal limbs, wherein the transverse limbs and longitudinal limbs are formed by curing after impregnating basalt fiber bundles with resin, and the cross sections of the transverse limbs and longitudinal limbs are flat; the surfaces of the transverse limbs and longitudinal limbs are hydrophilic surfaces, and sand and gravel are adhered to the hydrophilic surfaces of the transverse limbs and longitudinal limbs.

[0008] The particle size of sand and gravel is 10-50 mesh

[0009] The meshes formed between the transverse limbs and the longitudinal limbs are square or rectangular.

[0010] The mesh formed between the transverse limbs and the longitudinal limbs is square and has a size of 50-100 mm.

[0011] The thickness of the transverse limbs is consistent with that of the longitudinal limbs; the thickness of the nodes and non-nodes formed by the intersection of the transverse limbs and the longitudinal limbs is consistent.

[0012] The utility model also provides a concrete component, comprising concrete and structural steel bars cast in the concrete, wherein the concrete is also provided with the above-mentioned basalt fiber reinforced composite material grid for concrete crack resistance, and the basalt fiber reinforced composite material grid for concrete crack resistance is arranged on the outside of the structural steel bars.

[0013] A first concrete pad for controlling the distance between the basalt fiber reinforced composite material grid for concrete anti-cracking and the structural steel bar is arranged between the basalt fiber reinforced composite material grid for concrete anti-cracking and the structural steel bar.

[0014] A second concrete pad for controlling the distance between the basalt fiber reinforced composite material grid for concrete anti-cracking and the outer surface of the concrete component is arranged outside the basalt fiber reinforced composite material grid for concrete anti-cracking.

[0015] The characteristic is that the thickness of the first concrete pad and the second concrete pad are adjustable, and the total thickness is fixed to the design thickness of the concrete outside the structural reinforcement.

[0016] Compared with the prior art, the beneficial effects of the utility model are:

[0017] 1. The utility model of the basalt fiber reinforced composite material grid for concrete crack resistance uses basalt fiber as raw material, which is closer to the thermal expansion coefficient of concrete and will not generate internal stress due to temperature changes caused by the hydration heat of concrete, thereby reducing the possibility of concrete cracking. The surface of the transverse limbs and the longitudinal limbs is a hydrophilic surface, which improves the chemical bonding force between the limbs and the concrete and enhances the bonding performance. Sand and gravel are adhered to the hydrophilic surface of the transverse limbs and the longitudinal limbs to increase the friction between the limbs and the concrete and enhance the bonding performance.

[0018] 2. The utility model of the basalt fiber reinforced composite material grid for concrete crack resistance has a set mesh size so that the restraining force of the basalt fiber reinforced composite material grid is fully covered, which is beneficial to limit the development of cracks that have already appeared.

[0019] 3. The concrete component of the utility model controls the thickness of the concrete protective layer through the second concrete pad to prevent cracks from appearing on the outside of the concrete. The cracks in the concrete are caused by the temperature difference between the inside and the outside. The tensile stress of the concrete on the outside is large, and the cracks first appear on the outside of the concrete. By arranging a smaller concrete protective layer thickness and combining the mesh size, the mesh can be directly used at the maximum tensile stress of the concrete, giving full play to the excellent tensile properties of the fiber-reinforced composite material and improving the anti-cracking effect of the product. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention.

[0021] In the attached picture:

[0022] Figure 1 A schematic diagram of a basalt fiber reinforced composite grid structure based on concrete crack resistance;

[0023] Figure 2 This is a schematic diagram of the cross section of the limb in the utility model;

[0024] Figure 3 This is a schematic diagram of the limb node in the utility model;

[0025] Figure 4 It is a top view of the structure of the basalt fiber reinforced composite material grid arranged in concrete according to the utility model;

[0026] Figure 5 This is a structural cross-sectional view of the utility model of basalt fiber reinforced composite material grid arranged in concrete;

[0027] The components represented by the reference numerals in the figure are:

[0028] 1. Horizontal limbs, 2. Longitudinal limbs, 3. Basalt fiber bundles, 4. Resin, 5. Nodes, 6. Sand and gravel, 7. Mesh, 8. Basalt fiber reinforced composite mesh, 9. Structural steel bars, 10. Concrete cover, 11. Formwork, 12. Concrete pads. DETAILED DESCRIPTION

[0029] The following will describe the technical solution in the embodiment of the present invention in detail with reference to the accompanying drawings in the embodiment of the present invention: Example

[0030] See also Figure 1-3 This embodiment provides a basalt fiber reinforced composite material grid for concrete crack resistance, including a transverse limb 1 and a longitudinal limb 2. The cross-sections of the transverse limb 1 and the longitudinal limb 2 are both flat, and the thickness of the transverse limb 1 and the longitudinal limb 2 is 1-5 mm. The thickness is adjusted by the amount of fiber. The transverse limb 1 and the longitudinal limb 2 are both composed of a resin matrix and parallel basalt fiber bundles 3 cured in the resin matrix, and are impregnated with resin 4 and then cured. The transverse limb 1 and the longitudinal limb 2 are intersected, overlapped, and integrally formed. The gap between the transverse limb 1 and the longitudinal limb 2 is a mesh 7.

[0031] The impregnating resin 4 is preferably a modified epoxy resin, which is resistant to acid and alkali corrosion and has a strong bonding force with the fiber interface. The overall mechanical properties can meet the requirements of engineering construction.

[0032] The one-piece molding process is compression molding, with short high-temperature curing time, fast production speed, continuous production, stable product performance, high node strength and structural rigidity.

[0033] The position where the transverse limb 1 and the longitudinal limb 2 intersect is a node 5, and the thickness of the fibers at the node 5 and the non-node is consistent through molding.

[0034] The transverse limbs 1 and the longitudinal limbs 2 are modified by being impregnated with a hydrophilic agent, preferably a non-ionic surfactant, and the modification can improve the chemical bonding force between the limbs and the concrete and enhance the bonding performance.

[0035] The transverse limbs 1 and the longitudinal limbs 2 are sandblasted to form a rough surface structure, preferably garnet sand. Sandblasting can increase the friction between the limbs and concrete and enhance the bonding performance.

[0036] The transverse limbs 1 and the longitudinal limbs 2 are arranged vertically to each other, which is beneficial to enhancing the structural strength and making the basalt fiber reinforced composite material grid more solid.

[0037] The mesh 7 is square or rectangular, and the size is preferably 50mm*50mm. On the one hand, the limbs are denser and the restraining force is more evenly distributed. On the other hand, it does not hinder the passage of concrete aggregate. Example

[0038] This embodiment provides a concrete component. Figure 4-5, including concrete and a basalt fiber reinforced composite mesh 8 and structural steel bars 9 cast in the concrete, the basalt fiber reinforced composite mesh 8 is the basalt fiber reinforced composite mesh for concrete crack resistance provided in Example 1. The basalt fiber reinforced composite mesh 8 is continuously arranged on the outside of the structural steel bars 9, and can be arranged in parallel along the structural curved surfaces such as columns and piers, with a bending radius of not less than 32 cm. The basalt fiber reinforced composite mesh 8 constrains the tensile stress on the concrete surface through chemical bonding and mechanical bite with the concrete, limiting the appearance and development of cracks. Compared with the steel mesh in the prior art, the utility model can have better bonding performance and a smaller concrete protective layer thickness, and a better comprehensive crack control effect.

[0039] In one embodiment, the structural reinforcement 9 is formed by binding or welding main reinforcement and stirrups.

[0040] The concrete part outside the basalt fiber reinforced composite material grid 8 is a concrete protective layer 10, and the thickness of the concrete protective layer 10 is 20-40 mm, preferably 20 mm. The basalt fiber reinforced composite material grid is corrosion-resistant, and a smaller concrete protective layer thickness can be set to achieve better anti-cracking effect and avoid surface development of the component concrete.

[0041] The thickness of the concrete protective layer 10 is the distance from the basalt fiber reinforced composite material grid 8 to the formwork 11, and is controlled by the size of the concrete pads 12 tied to the grid 8. The concrete pads 12 should have a strength not lower than that of the concrete of the structure body. When tied, they are perpendicular to the steel bars and the grid. The size should be determined in combination with the thickness of the concrete protective layer 10 required by the design and the overall stress conditions.

[0042] The main force direction of the installed basalt fiber reinforced composite material grid 8 should be perpendicular to the surface of the concrete component to facilitate stress transfer and uniform distribution. First, tie the concrete pad 12 on the structural steel bar 9, which is used to fix and support the spatial positioning of the grid. After the concrete pad 12 is tied to the structural steel bar 9, it is tied to the basalt fiber reinforced composite material grid 8 through the wire, and then the pad is tied on the other side of the grid to ensure the distance from the grid to the concrete surface, that is, the template 11. The shapes and sizes of the pads on both sides can be different, but they should be staggered and dispersed between the steel bars and the template 11. They should not be laid across the entire cross-section of the concrete protective layer. The pads on both sides of the basalt fiber reinforced composite material grid 8 should be staggered 3-5cm for binding.

[0043] The concrete pad 12 should be firmly tied to the structural steel bar 9 or the basalt fiber reinforced composite material grid 8, and the binding wire and its wire head should not enter the concrete protective layer to avoid adverse effects on the concrete; when tying, the pad should be perpendicular to the steel bar and the grid, unless there are special provisions in the design, so as to better control the thickness of the concrete protective layer. The basalt fiber reinforced composite material grid should be arranged continuously throughout the entire length. If the grid length is insufficient and overlap is required, transverse or circumferential overlap can be used. At the same time, the overlap length must be more than 3 nodes. It is advisable to use steel wire or nylon binding wire to tie in a cross-shaped manner with double diagonals. The three intersections can be tied in a plum blossom style every other wire to ensure the overlap quality and overall firmness. Before pouring concrete, it should be checked and confirmed that the grid has no displacement, looseness, breakage, wrinkles, etc., and the installation quality meets the construction requirements.

[0044] The above is only a preferred specific implementation of the utility model, but the protection scope of the utility model is not limited thereto. Any changes or additions, subtractions or substitutions that can be easily thought of by any technician familiar with the technical field within the technical scope disclosed by the utility model should be included in the protection scope of the utility model. Therefore, the scope of the utility model is defined by the attached claims and their equivalents.

Claims

1. A basalt fiber reinforced composite material grid for concrete crack resistance, comprising transverse limbs (1) and longitudinal limbs (2), characterized in that: The transverse limbs (1) and the longitudinal limbs (2) are both formed by impregnating basalt fiber bundles (3) with resin (4) and then curing them. The cross-sections of the transverse limbs (1) and the longitudinal limbs (2) are flat. The surfaces of the transverse limbs (1) and the longitudinal limbs (2) are hydrophilic surfaces, and sand and gravel (6) are adhered to the hydrophilic surfaces of the transverse limbs (1) and the longitudinal limbs (2).

2. The basalt fiber reinforced composite material grid for concrete crack resistance according to claim 1, characterized in that: The particle size of the sand and gravel (6) is 10-50 mesh.

3. The basalt fiber reinforced composite material grid for concrete crack resistance according to claim 1, characterized in that: The mesh (7) formed between the transverse limbs (1) and the longitudinal limbs (2) is square or rectangular.

4. The basalt fiber reinforced composite material grid for concrete crack resistance according to claim 3, characterized in that: The mesh (7) formed between the transverse limbs (1) and the longitudinal limbs (2) is square and has a size of 50-100 mm.

5. The basalt fiber reinforced composite material grid for concrete crack resistance according to any one of claims 1 to 4, characterized in that: The thickness of the transverse limbs (1) and the longitudinal limbs (2) are consistent; the thickness of the nodes (5) formed by the intersection of the transverse limbs (1) and the longitudinal limbs (2) and the thickness of the non-nodes are consistent.

6. A concrete member, comprising concrete and structural steel bars cast in the concrete, characterized in that: The concrete is also provided with a basalt fiber reinforced composite material grid for concrete crack resistance as claimed in any one of claims 1 to 5, and the basalt fiber reinforced composite material grid for concrete crack resistance is arranged on the outside of the structural steel bars.

7. The concrete component according to claim 6, characterized in that A first concrete pad for controlling the distance between the basalt fiber reinforced composite material grid for concrete anti-cracking and the structural steel bar is arranged between the basalt fiber reinforced composite material grid for concrete anti-cracking and the structural steel bar.

8. The concrete component according to claim 7, characterized in that A second concrete pad for controlling the distance between the basalt fiber reinforced composite material grid for concrete anti-cracking and the outer surface of the concrete component is arranged outside the basalt fiber reinforced composite material grid for concrete anti-cracking.

9. The concrete component according to claim 8, characterized in that The thickness of the first concrete pad and the second concrete pad are adjustable, and the total thickness is fixed to the design thickness of the concrete outside the structural reinforcement.

Citation Information

Patent Citations

  • Anti-crack method for concrete protecting layer

    CN103321422B